2017
DOI: 10.1071/py17063
|View full text |Cite
|
Sign up to set email alerts
|

Review of patient-reported experience within Patient-Centered Medical Homes: insights for Australian Health Care Homes

Abstract: Abstract. Understanding patient experience is necessary to advance the patient-centred approach to health service delivery. Australia's primary healthcare model, the 'Health Care Home', is based on the 'Patient-Centered Medical Home' (PCMH) model developed in the United States. Both these models aim to improve patient experience; however, the majority of existing PCMH model evaluations have focussed on funding, management and quality assurance measures. This review investigated the scope of evidence reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Participants identified HCHs' potential to encourage continuity of care, a view supported by evidence from Patient-Centred Medical Home (PCMH) implementation in the USA. [12][13][14] While patients believe continuity improves the doctor-patient relationship, 15,16 the participants identified that building relationships requires time, which may be compromised by funding shifting care delivery away from the GP. Some GPs anticipated benefit from patients developing relationships with other care providers, provided there was effective communication among a GP-led team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants identified HCHs' potential to encourage continuity of care, a view supported by evidence from Patient-Centred Medical Home (PCMH) implementation in the USA. [12][13][14] While patients believe continuity improves the doctor-patient relationship, 15,16 the participants identified that building relationships requires time, which may be compromised by funding shifting care delivery away from the GP. Some GPs anticipated benefit from patients developing relationships with other care providers, provided there was effective communication among a GP-led team.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding PCMH patients' experience in relation to patient-provider and patient-practice relationships in the USA is mixed, and this issue deserves further consideration. 14 The participants reported practical struggles associated with HCH implementation. Previous literature anticipated difficulties concerning the transformation process, electronic health records, funding, and practice structure and resources.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from implementation studies of the Medical Home in the US has demonstrated some improvement in preventative care service delivery for people with chronic conditions, although results are mixed and insufficient for service provision (including accessibility and coordination of care), clinical outcomes, in-patient utilisation 41 and patient experience. 42 Diversity in the primary care setting has challenged implementation of the Medical Home care model, indicating a need for setting-specific approaches to address the healthcare needs of distinctive population subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The time and resources required to implement the model and to transform work processes incur substantial costs, both one-time and ongoing (5,15,16). Studies that examine patient experiences of PCMH have been mainly limited to patient-provider relationship and access to care, whereas other aspects such as patient engagement, activation, shared decision-making and patient experience with other practice staff have received less investigation (17).…”
Section: Introductionmentioning
confidence: 99%